2021
DOI: 10.1016/j.watres.2021.117435
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of SARS-CoV-2 along wastewater and sludge treatment processes

Abstract: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is shed in the feces of infected people. As a consequence, genomic RNA of the virus can be detected in wastewater. Although the presence of viral RNA does not inform on the infectivity of the virus, this presence of genetic material raised the question of the effectiveness of treatment processes in reducing the virus in wastewater and sludge. In this work, treatment lines of 16 wastewater treatment plants were monitored to evaluate the removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 54 publications
7
46
3
3
Order By: Relevance
“…In addition, and in contrast to other research conducted on the presence of SARS-CoV-2 in sewage, our study aimed also at exploring the detection of the virus in the marine environment and the capacity of the WWTP to remove the virus (Galicia is well known for its fish, shellfish and aquaculture activities). Our results confirmed the capacity of the biological reactors and the disinfection system in WWTP to eliminate the virus (Balboa et al, 2021;Serra-Compte et al, 2021). The impact in the marine environment was of minor importance and the detection of the virus in seawater and wild and aquacultured mussels can be associated to uncontrolled discharge of wastewater and alleviation from the sewage network.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, and in contrast to other research conducted on the presence of SARS-CoV-2 in sewage, our study aimed also at exploring the detection of the virus in the marine environment and the capacity of the WWTP to remove the virus (Galicia is well known for its fish, shellfish and aquaculture activities). Our results confirmed the capacity of the biological reactors and the disinfection system in WWTP to eliminate the virus (Balboa et al, 2021;Serra-Compte et al, 2021). The impact in the marine environment was of minor importance and the detection of the virus in seawater and wild and aquacultured mussels can be associated to uncontrolled discharge of wastewater and alleviation from the sewage network.…”
Section: Discussionsupporting
confidence: 78%
“…Although the utilization of anaerobic digestion alone was ineffective in the elimination of EV (1 log reduction) and SARS-CoV-2, the combination of mesophilic anaerobic digestion and thermal hydrolysis has been regarded as one of the most effective approaches to virus inactivation [226] . Similarly, the recent work of Serra-Compte et al found the log removal of viruses during traditional digestion to be negative (mean values of −0.17 ± 0.89), while it was 1.69 ± 0.27 for thermal hydrolysis+anaerobic digestion, which is closely related to the inactivation of the viruses by saturated steam at 150–160 °C [227] . For sludge air-drying, the infectivity of viruses declined with the continuous increase in solid content [228] ; moreover, such inactivation was irreversible because of the disintegration of viral particles and release of RNA genomes.…”
Section: Removal Trends Of Viruses In Different Wwtp Unit Processesmentioning
confidence: 70%
“…Indeed, to date no viable virions have been isolated from posttreatment wastewater samples testing positive for SARS-CoV-2 by molecular assays, 24 and most studies have confirmed the complete removal of viral RNA traces at the end of an MBR disinfection line. 11 , 20 , 59 …”
Section: Resultsmentioning
confidence: 99%